Analysis of financial growth in manufacturing companies across three Nordic countries - Hilmola, Olli-Pekka; Fjellström, Daniella; Hilletofth, Per (Frontiers in Applied Mathematics and Statistics, 2025)
The three Nordic countries (Denmark, Finland, and Sweden) have long enjoyed economic success in manufacturing and innovation. All of these countries have small domestic markets and depend on international trade. Before the Global Financial Crisis (GFC; 2008–2009), Finland and Sweden set the standards, but since the GFC, Denmark has performed particularly well, while Sweden has had a mediocre performance. Growth is evident not only in revenues but also in profits and asset amounts. This growth has been consistent across many companies and has followed a linear pattern. Finland has generally performed worse than the other two countries, with issues mostly associated with lower revenue and profit growth, and changes in assets. Finland lacks companies with consistent growth. A key difference from Denmark is the smaller presence of the healthcare sector. The present analysis indicated that consistent growth is required to achieve the desired results using the current measures.